2021
DOI: 10.3390/v13061128
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Virotherapy Treatment of Breast Cancer: Barriers and Recent Advances

Abstract: Oncolytic virotherapy (OV) is an emerging class of immunotherapeutic drugs. Their mechanism of action is two-fold: direct cell lysis and unmasking of the cancer through immunogenic cell death, which allows the immune system to recognize and eradicate tumours. Breast cancer is the most common cancer in women and is challenging to treat with immunotherapy modalities because it is classically an immunogenically “cold” tumour type. This provides an attractive niche for OV, given viruses have been shown to turn “co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Much research is being carried out in order to study several different OV platforms for the potential treatment of TNBC. OVs being studied in BCs not classified as TNBC will not be described here, though recent reviews of these viruses are available [ 115 , 116 ]. Below, currently described viruses tested against TNBC preclinically in vitro and in vivo, as well as those currently in human clinical trials, are summarized.…”
Section: Preclinical Ovs For Tnbcmentioning
confidence: 99%
“…Much research is being carried out in order to study several different OV platforms for the potential treatment of TNBC. OVs being studied in BCs not classified as TNBC will not be described here, though recent reviews of these viruses are available [ 115 , 116 ]. Below, currently described viruses tested against TNBC preclinically in vitro and in vivo, as well as those currently in human clinical trials, are summarized.…”
Section: Preclinical Ovs For Tnbcmentioning
confidence: 99%
“…Clinical studies conducted in melanoma patients indicated that there is a response to OncoVEX GM-CSF not just in injected lesions but also in distant metastases, defining a so-called abscopal effect ( 37 , 91 ). Talimogene laherparevac (T-Vec) expresses GM-CSF thereby stimulating cytokine production and potentially activating the immune response, and perhaps offering itself to combinations with immune checkpoint inhibitors ( 92 ).…”
Section: Published Clinical Trials With Oncolytic Viruses In Breast Cancermentioning
confidence: 99%
“…For decades, effective implementation strategies have been developed to optimize the advancements in the fields of tumor survivorship, diagnosis, treatment, and end-of-life care [10]. For instance, a series of treatments have been developed to conquer cancers with high uncontrolled cell division and heterogeneity, including surgery (e.g., laparoscopic rectal surgery and robotic surgery) [11,12], photothermal therapy (PTT) [13][14][15], radiotherapy [16], chemotherapy [17], oncolytic virotherapy [18], RNA vaccine [19,20], hormone therapy [21], peptide-based neoantigen vaccine [22,23], gene therapy [24][25][26], immunotherapy (e.g., immune cells and checkpoint inhibitors) [2], and even nanomaterial-mediated nanotheranostics (e.g., organic nanomaterials, inorganic nanomaterials, and organic-inorganic hybrid nanomaterials). Nevertheless, the aforementioned strategies have also revealed inherent shortcomings (e.g., severe toxicity, off-target effects, graft-versus-host disease, and drug delivery barriers), which collectively hinder the further improvement in cancer administration [27,28].…”
Section: Introductionmentioning
confidence: 99%